Az „Új Európai Rend“ a japán jogtörténti kutatásokban - Sato, Dan (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2025)
Since 1933, National Socialist jurisprudence had been the subject of much interest and controversy among Japanese legal scholars. Even the Japanese Ministry of Justice examined and translated a series of National Socialist legislation and literature for reference purposes. During the National Socialist era, a young Japanese professor of law named Satoshi Nishimoto visited Germany. While studying in Munich, this scholar witnessed unprecedented activity in the field of Germanic legal history, which at that time was combined with geopolitics. After returning to Japan, he attempted to apply this method of legal history to his own country. However, these efforts ended in failure.